“THE TWISTED FORMS OF THE MACHO”. OLD AGE AND SEXUAL DISSIDENCE IN BELLEZO (YO ME MUERO SIN PATRIA) BY RAGGS - Leonardo-Loayza, Richard (2025)
In recent years, there has been an increase in studies focusing on the LGBTQ+ community. However, one underexplored topic in this field is the relationship between old age and homosexuality. Latin American literature is no exception; few books have addressed this relationship. One text that addresses this topic is Bellezo (yo me muero sin patria) (2023) by RAGGS, the pseudonym of Rafael García-Godos Salazar (Lima, 1979). The objective of the following article is to analyze the representation of the older sexual dissident in the RAGGS poetry collection. It is proposed that this collection of poems is important because it is one of the first literary works to address the aging of sexual dissidents in Peru. While this is true, it is also true that the representation of this condition is problematic because it reiterates some of the stereotypes that have served heterosexuals to subordinate homosexuals, as they are portrayed as hypersexualized individuals, dependent on their bodies. In the world represented in the collection of poems, sexual dissidents are only fulfilled beings in their youth, when their bodies are desirable and they can have sexual relations. Once they grow older, their lives cease to have meaning because their bodies are no longer attractive to others. To develop the proposed analysis, some contributions from the studies of sexual dissidence, homoeroticism, and queer studies are drawn upon.